SIRT6 expression and oxidative DNA damage in individuals with prediabetes and type 2 diabetes mellitus - Çalışkan, Z.; Mutlu, T.; Güven, M.; Tunçdemir, M.; Niyazioğlu, M.; Hacioglu, Y.; Dincer, Y. (Gene, 2018)
Sirtuins (SIRTs) is a family of NAD+ dependent histone deacetylases. SIRT6 takes play in glucose homeostasis, genomic stability and DNA repair. Although increased oxidative DNA damage and decreased DNA repair activity were determined in diabetes mellitus, the possible relation between level of oxidative DNA damage and SIRT6 expression has not been investigated so far. We determined SIRT6 expression and urinary 8-hydroxy deoxyguanosine (8-OHdG) levels, marker of oxidative DNA damage, in cases with prediabetes (PreDM) and type 2 diabetes mellitus (T2DM). SIRT6 gene expression was determined in peripheral blood leukocytes of 70 patients with type 2 diabetes, 50 cases in prediabetic stage and 40 healthy subjects. SIRT6 mRNA levels were determined by quantitive real time- polymerase chain reaction. SIRT6 protein was detected by immunocytochemical staining. Urinary 8-hydroxy deoxyguanosine (8-OHdG) levels were measured by ELISA. There was no significant difference between groups for SIRT6 mRNA level. SIRT6 immunopositivity in T2DM group was lower when compared to those in preDM group (P<0.05). SIRT6 positive cell number in T2DM and preDM groups were lower in comparison to control group (P<0.01 for both), however, when study groups were subdivided into two groups according to their age, the difference between preDM and control groups disappeared in both mid-aged and old-aged groups. The urinary 8-OHdG level was found to be higher in the T2DM group in comparison to preDM group (P<0.05). When age is taken into consideration, urinary 8-OHdG level in the T2DM group was found to be higher than those in both preDM and control groups in the old-aged cases but no significant difference was determined between groups in the mid-aged cases. There was no relation between SIRT6 expression and urinary 8-OHDG excretion. It was concluded that SIRT6 may take play in development of T2DM but this effect seems to be independent from repair of oxidative DNA damage. •SIRT6 protein level is reduced in individuals with pre-diabetes.•SIRT6 protein level is reduced in patients with T2DM.•As a regulator of gene expression, SIRT6 may take play in development T2DM.